2009
DOI: 10.1007/s00213-009-1569-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of fatty acid amide hydrolase reduces reinstatement of nicotine seeking but not break point for nicotine self-administration—comparison with CB1 receptor blockade

Abstract: These results indicate that the integrity of the CB(1) receptors is necessary for the incentive motivation of the rats for nicotine and that FAAH inhibition may be as effective as CB(1) receptor blockade to prevent reinstatement of nicotine seeking. Since FAAH inhibition present antidepressant and anxiolytic properties in rodents, targeting the FAAH may represent a novel strategy to prevent relapse for tobacco smoking that may be better tolerated than rimonabant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
114
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(126 citation statements)
references
References 61 publications
11
114
1
Order By: Relevance
“…This is presumably the mechanism by which PPARa activation blocks the dopaminergic effects of nicotine in the VTA and nucleus accumbens shell, which are believed to provide the primary basis for nicotine reward (Gotti et al, 2010;Corrigall et al, 1994;Lecca et al, 2006). This nicotineinduced dopaminergic signaling, and indeed the rewarding effects of nicotine in behavioral procedures, have been shown to be blocked by experimental drugs that activate PPARa directly (ie, the synthetic agonist WY14643, the endogenous ligands oleoylethanolamine and palmitoylethanolamide, and the longer-acting oleoylethanolamine derivative methyl oleoylethanolamine; Melis et al, 2008Melis et al, , 2010Mascia et al, 2011) or indirectly (ie, the fatty-acid amide hydrolase inhibitor URB597; Melis et al, 2008;Scherma et al, 2008;Forget et al, 2009;Luchicchi et al, 2010). The electrophysiology, microdialysis, and behavioral experiments of this study extend these findings to the fibrate class of medications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is presumably the mechanism by which PPARa activation blocks the dopaminergic effects of nicotine in the VTA and nucleus accumbens shell, which are believed to provide the primary basis for nicotine reward (Gotti et al, 2010;Corrigall et al, 1994;Lecca et al, 2006). This nicotineinduced dopaminergic signaling, and indeed the rewarding effects of nicotine in behavioral procedures, have been shown to be blocked by experimental drugs that activate PPARa directly (ie, the synthetic agonist WY14643, the endogenous ligands oleoylethanolamine and palmitoylethanolamide, and the longer-acting oleoylethanolamine derivative methyl oleoylethanolamine; Melis et al, 2008Melis et al, , 2010Mascia et al, 2011) or indirectly (ie, the fatty-acid amide hydrolase inhibitor URB597; Melis et al, 2008;Scherma et al, 2008;Forget et al, 2009;Luchicchi et al, 2010). The electrophysiology, microdialysis, and behavioral experiments of this study extend these findings to the fibrate class of medications.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that experimental drugs that activate PPARa block nicotine-induced firing of dopamine neurons in the VTA and nicotine-induced elevations of extracellular dopamine levels in the nucleus accumbens shell of rats, and that they decrease nicotine-seeking behavior in rats and monkeys (Melis et al, 2008Scherma et al, 2008;Forget et al, 2009;Luchicchi et al, 2010;Mascia et al, 2011). These preclinical findings suggest that PPARa could be an effective target for anti-smoking medications.…”
Section: Introductionmentioning
confidence: 91%
“…Screening of two independent clinical populations revealed that CB 1 gene variants are associated with nicotine dependence (Chen et al, 2008) and the CB 1 receptor antagonist Rimonabant (SR141716A) prolonged abstinence rates in smokers expressing motivation to quit . SR141716A and the related CB 1 antagonist AM251 reduce nicotine selfadministration (SA) by rats (Cohen et al, 2002(Cohen et al, , 2005Forget et al, 2009;Shoaib, 2008), attenuate nicotine-induced increases in nucleus accumbens (NAc) dopamine (DA) (Cheer et al, 2007;Cohen et al, 2002;Grieder et al, 2012), and reduce reinstatement of nicotine-seeking behavior in animal models of relapse (Forget et al, 2009). Collectively, these findings provide strong evidence for a CB 1 receptor involvement in the motivational effects produced by nicotine, and imply a role for endocannabinoid (eCB) signaling in this process.…”
Section: Introductionmentioning
confidence: 93%
“…For example, although synthetic CB 1 agonists increase nicotine SA and enhance nicotine-seeking behavior (Gamaleddin et al, 2012), these nicotine-related behaviors are generally attenuated by enhancing endogenous eCB tone (eg, eCB clearance inhibition) (Forget et al, 2009;Gamaleddin et al, 2011;Scherma et al, 2008). The distinction between these influences may arise, in part, from differential regional patterns of CB1 activation.…”
Section: Endocannabinoid Levels Following Nicotine Exposure Mw Buczynmentioning
confidence: 99%
See 1 more Smart Citation